Simulated leaf area growths of immature rubber, banana and pineapple intercropping using surhis model - Jalloh, Mohamadu Boyie; Wan Harun, Wan Sulaiman; Talib, Jamal; Ramlan, Mohd Fauzi; Teh, Christopher Boon Sung (2007)
Intercropping is not fancied in high input agriculture of developed countries but it is widely practiced in the agriculture of developing countries. It is now being accepted that well managed intercropping systems are stable and sustainable. An ecophysiological model using the Fortran Simulation Environment (FSE) was used to simulate the leaf area growth of an intercropping system of immature-rubber, banana and pineapple under potential crop growth conditions. The leaf growth for each crop was smimulated based on the amount of dry matter partitioned to the leaves after after respiratory losses were discounted from individual crop light interception and carbohydrate assimilation of the intercrop. At 600 days after planting (DAP) the simulated leaf index (LAI) of rubber and pineapple was on average 1.4 respectively. The simulated LAI for the parent crop of banana was about 4.3 at peak growth (150 DAP), and at the same time the simulated LAI of the first ratoon crop was about 2.7. The mean absolute error (MAE) between simulated and observed LAI for rubber, mother banana, first ratoon banana and pineapple was 7.7%, 15.2%, 27% and 6.4% respectively. This indicates that the leaf area index was simulated with good accuracy but there is scope for improvement.